(untitled) - Janna, William S. (Boston, 2015)
This book is designed to serve senior-level engineering students taking a capstone design course in fluid and thermal systems design. It is built from the ground up with the needs and interests of practicing engineers in mind; the emphasis is on practical applications
Keywords: Trao đổi nhiệt,Piping,Heat exchangers,Đường ống; Thiết kế và xây dựng,Design and construction.,Design and construction.,Thiết kế và xây dựng